Cactus cladodes (Opuntia humifusa) extract minimizes the effects of UV irradiation on keratinocytes and hairless mice - Kyungmi Park; Hyeon-Son Choi; Yang Hee Hong; Eun Young Jung; Hyung Joo Suh (Pharmaceutical Biology, 2017)
Context: Cactus cladodes [Opuntia humifusa (Raf.) Raf. (Cactaceae)] is one of the cactus genera, which has long been used as a folk medicine for skin disorders. Objective: This study investigated the skincare potential of cactus cladodes extract (OHE), including its ability to regulate ultraviolet B (UVB)-induced hyaluronic acid (HA) production. Materials and methods: Gene expression levels of hyaluronic acid synthases (HASs) and hyaluronidase (HYAL) were measured in UVB-irradiated HaCaT cells with OHE treatment (10, 25, 50, 100 μg/mL) by real-time polymerase chain reaction (PCR). The HA content was analyzed in hairless mice (SKH-1, male, 6 weeks old) treated with OHE for 10 weeks by using enzyme-linked immunosorbent assay (ELISA). Haematoxylin and eosin (H&E) and immunohistological staining were performed to examine epidermal thickness and levels of CD44 and hyaluronic acid-binding protein (HABP). Results: HA synthases (HAS,1 HAS2, HAS3) mRNA levels were increased by 1.9-, 2.2- and 1.6-fold, respectively, with OHE treatment (100 μg/mL), while UVB-induced increase of hyaluronidase mRNA significantly decreased by 35%. HA content in animal was decreased from 42.9 to 27.1 ng/mL by OHE treatment. HAS mRNA levels were decreased by 39%, but HYAL mRNA was increased by 50% in OHE group. CD44 and HABP levels, which were greatly increased by UVB-irradiation, were reduced by 64 and 60%, respectively. Epidermal thickness, transepidermal water loss (TEWL), and erythema formation was also decreased by 45 (45.7 to 24.2 μm), 48 (48.8 to 25 g/h/m2) and 33%, respectively. Conclusion: OHE protects skin from UVB-induced skin degeneration in HaCaT cells and hairless mice.